Cancer survivorship in low- and middle-income countries: challenges, needs, and emerging support strategies - Gustavo Rodrigues dos Anjos; Gustavo Rodrigues dos Anjos; Guilherme Falcao Machado; Guilherme Falcao Machado; Cassiano Pereira de Barros; Cassiano Pereira de Barros; Victor Piana de Andrade; Rui Monteiro de Barros Maciel; Lucas Leite Cunha; Lucas Leite Cunha; Lucas Leite Cunha (Frontiers in Public Health, 2025)
Cancer survivorship has become a critical global health issue, with survival rates on the rise in both high-income countries (HICs) and low- and middle-income countries (LMICs). Cancer survivors, encompassing individuals from diagnosis onward, face unique and complex health challenges that necessitate tailored care. In HICs, survival rates have increased due to advances in diagnosis and treatment, prompting robust survivorship programs addressing late effects and long-term quality of life. In LMICs, however, disparities in healthcare access, infrastructure, and support systems hinder comparable progress in survivorship care, particularly outside urban areas. LMIC survivors often contend with financial barriers, limited access to follow-up care, and significant psychosocial and rehabilitative gaps. Specialized survivorship centers are rare, and resources for addressing late effects are constrained, impacting survivors' long-term wellbeing. Emerging studies, primarily from middle-income nations, identify late effects such as endocrine and metabolic disorders, though robust, comprehensive data remain scarce. For childhood cancer survivors, late effects like chronic viral infections and cognitive impairments are documented, yet systematic follow-up remains limited. To bridge these gaps, LMICs require innovative care models, such as non-profit partnerships and community-based interventions, to meet the complex needs of survivors. In Brazil, we've highlighted successful programs including the Mais Médicos program for increased care capacity and DATA-SUS as a model registry. This review synthesizes available literature on cancer survivorship in LMICs, evaluating challenges and successful practices across diverse regions. Addressing these needs is crucial for improving survivorship care, particularly in regions where socioeconomic disparities amplify the challenges of post-cancer recovery.